Mechanics and Electrodynamics of Magneto- and Electro-elastic Materials - Ogden, Ray W.; Steigmann, David J.; SpringerLink (Online service) (Vienna : Springer Vienna, 2011)
This volume presents a state-of-the-art overview of the continuum theory of both electro- and magneto-sensitive elastomers and polymers, which includes mathematical and computational apsects of the modelling of these materials from the point of view of material properties and, in particular, the "smart-material" control of their mechanical properties.
Keywords: Engineering; Computer science; Materials; Vibration; Engineering; Continuum Mechanics and Mechanics of Materials; Computational Science and Engineering; Materials Science, general; Vibration, Dynamical Systems, Control